Regions and firms in eWork Relocation Dynamics: Pittsburgh's call centre industry. (1st July 2007) - Chris Benner
Abstract : This paper attempts to contribute to our theoretical understanding of the relationship between regions and the location dynamics of telemediated employment through an analysis of the regional dynamics shaping the call centre industry in Pittsburgh, which has grown significantly despite the increased possibilities for offshoring. Focussing on fundamental dimensions of the call centre labour process, it suggests that there are particular features of the Pittsburgh region that are not only important components of firms' decisions to locate call centre work there but also influence their processes for doing so. These features are rooted in the industrial history, socio-demographic dynamics and cultural factors in the region that increase the level of 'stickiness', or propensity of enterprises to stay in the area.